Sustainable product purchase: does information about product sustainability on social media affect purchase behavior? - Muhammad Amad Saeed; Ammara Farooq; Wolfgang Kersten; Semah Ibrahim Ben Abdelaziz (Asian Journal of Sustainability and Social Responsibility (AJSSR), 2019)
Nowadays, consumer-to-consumer communication and its impact on purchase decisions have gained substantial consideration owing to digitalization and the emergence of internet-based social media platforms. Social media allows consumers to communicate with thousands of people well beyond their network. Consequently, the demand for transparency from industrial corporations has increased. It even becomes more important to understand how sustainability-related information on social media holds organizations accountable for their wrongdoings and reward them for taking sustainability-related initiatives. In this research work, the authors investigate how information that is available on social media influences consumers' purchase behavior with regard to sustainable products in the context of developing countries. Therefore, the authors surveyed social media users residing in Pakistan and used partial least squares structural equation modeling (PLS-SEM) to analyze the collected data. The results established that positive and negative sustainability-related information on social media significantly influences consumers' intention to purchase sustainable products. Furthermore, this study explains that consumers' willingness to seek sustainability-related information makes them dependent on social media and this dependency on social media affects their intention to purchase.
Keywords: 650; Sustainable product development; Social media; Consumer purchase behavior; Sustainability risk; Sustainability trust; Media system dependency theory